Diseases of shade trees - Tattar, Terry A. (Academic Press, 1978)
Diseases of Shade Trees provides an introduction to tree diseases for students and others concerned with the care of shade and ornamental trees. Diseases of woody plants fall into two major categories: infectious diseases and noninfectious diseases. Part I of the book presents the infectious pathogens and the diseases they cause. These include bacteria, mycoplasmas, nematodes, seed plants, and viruses. The nature of the fungi is also presented, with separate chapters for leaf, root, rust, stem, and wilt diseases caused by fungi. Wound diseases, which are associated with both fungi and bacteria.